Institutionalizing Cultural Funding at the Level of the Local Government in the Philippines - Gina S. Salazar (Lembaga Penelitian Universitas Pasundan, 2015)
The major purpose of the study is to outline how the institutionalization of funding for Culture and the Arts could be operationalized at the Local Government Units (LGUs) in the Philippines to facilitate the sustainability of cultural programs in Philippine localities. More specifically, this study aims to discuss the status of cultural funding in the Philippines and the challenges that beset the LGUs in operationalizing cultural funding at their level. Using the qualitative approach, the study proceeds with the analysis of the status of cultural funding in the Philippines; data are derived by the researcher as a participant-observer during a national training on Culture-based governance participated in by executives and tourism officers from Philippine LGUs. Gender- Responsive Budgeting is presented as a case of an institutionalized mechanism for financing gender concerns in the country, an illustration of the possibility of implementing institutionalized funding for Culture and the Arts at the level of the LGUs. The operationalization of the institutionalization of cultural funding is then outlined; challenges associated with the process of institutionalizing Culture and the Arts funds are analyzed using Thomas Schmitt’s general framework for the analysis of fields of governance; and recommendations are made as to how these challenges are to be confronted by the LGUs. The institutionalization of cultural funding can only be ultimately realized for the LGUs via a Republic Act. A requisite external to institutionalization is the process of reforming mindsets in understanding Culture and its role in human development; and in shifting existing beliefs to the idea that effective Cultural Governance is equivalent to institutionalizing cultural funding at the Philippine LGUs. Keywords: Cultural Funding, Institutionalization, Funds for Culture, Philippine Local Government, Local Government Funding